STRATEGI DINAS TENAGA KERJA DALAM MENGURANGI ANGKA PENGANGGURAN DI MASA PANDEMI COVID-19 - Siti Nuraini; Dhuwi Puspitasari (Governance, 2022)
This study aims to examine and explain how the Department of Manpower's strategy is to reduce unemployment during the Covid-19 pandemic in Bekasi City. This research was motivated by the phenomenon of the spread of the Covid-19 pandemic which resulted in an increase in the open unemployment rate in Bekasi City. One of the causes is Termination of Employment (PHK) by the company. The research method used by researchers in this study is a qualitative research method with a descriptive approach. Data collection techniques used in this study were observation, in-depth interviews and documentation. The source of the data obtained came from 4 employee informants of the Bekasi City Manpower Office. The results of this study indicate that the strategy carried out by the Bekasi City Manpower Office in reducing unemployment during the Covid-19 pandemic is to provide job market information (job fairs) and hold job training programs, such as competency-based training, technology-based training and entrepreneurship training. The strategy implemented is good, but it is not effective enough to reduce the open unemployment rate in Bekasi City, because the open unemployment rate in Bekasi City is still increasing.